Figure skater level moderates balance training - Saunders, N. W.; Hanson, N. J.; Koutakis, P.; Chaudhari, A. M.; Devor, S. T. (International Journal of Sports Medicine, 2013)
It was suggested that baseline levels of postural control in figure skaters might influence the effectiveness of neuromuscular training. The aims of the present study were to investigate the baseline association of skater skill level with standard center of pressure metrics and time to stabilization, and to determine if skill level influenced the effectiveness of a 6-week neuromuscular training program. There was no main effect of skill level for any baseline center of pressure metric for either test. There was no main effect of skill level on the percent change in any metric for the single leg stance following training. However, skill level did influence landing test outcome measures. The difference in percent change of root mean squared was evident for the mediolateral (low: 24.5±16.50% vs. high: 2.42±14.99%) and anterior-posterior (low: 6.66±9.21% vs. high: - 4.03±5.91%) axes. Percent change in anterior-posterior time to stabilization also differed by skill level (low: - 0.73%±4.74 vs. high: - 5.61%±2.76). Note that this study was underpowered with 26 subjects and 14 subjects contributing to baseline and post-training assessments, respectively. Though no baseline differences in postural control were observed, compared with low skill levels, high skill levels benefitted more from training.